The Influence of service quality on behavioral intentions mediated by patient trust and satisfaction - Yuswanto, Subur; Azizah, Siti Nur (Jurnal Mantik, 2024)
This study aims to determine the effect of service quality on trust, consumer satisfaction and behavioral intentions in the patient population of PKU Muhammadiyah Gombong Hospital. The population is patients at the PKU Muhammadiyah Gombong Hospital with a sample of 100 inpatients. Questionnaires are distributed by distributing questionnaires directly to patients. SmartPLS software version 3 was used to model the relationships between the variables studied. The research results confirm the existence of a relationship between trust and behavioral intentions, consumer satisfaction and behavioral intentions, service quality and trust, service quality and consumer satisfaction. The research results show that there is a significant mediating effect of consumer trust and satisfaction on the relationship between service quality and behavioral intentions. Based on the model presented in this research, we can conclude that service quality has a major impact on trust, patient satisfaction and behavioral intentions